Uma Análise comparativa entre frameworks de persistência de dados em javascript - Rocha, Gustavo Clemente Colombo da (2022)
JavaScript is a programming language created in 1995 that gained strength mainly in the early 2010s and that changed the landscape of software development, both for web and mobile, becoming a great option for those who want to develop both on the client and server side and seeks flexibility. With the advancement of technology and the use of the internet, there is an increase in the creation of web and mobile applications that streamline everyday tasks and remove the need for a person to go to an establishment to perform an action, for example, a digital bank. With the growth of these digital solutions in software format, user requirements also increase, for example, system stability, quick response and security are basic and fundamental attributes for the use of a software, so in the development of a software it is necessary to be careful when choosing the database and persistence tools that handle this database, since it is in this area where all business rules and data must be implemented and maintained in a secure and easily accessible way. Currently, there are several data persistence frameworks consolidated in the developer community for software development that can implement one or both of the most used and traditional types of databases when developing a system, the relational database and the database. non-relational data. Before any line of code is written, it is necessary to keep in mind which functional and non-functional requirements need to be respected and implemented in the system, so that in later stages of development there is as little rework as possible, delays and even failure to be avoided. from the project. Therefore, the present work aims to make a comparison between 6 data persistence frameworks generating an artifact in table format that serves as a catalog for developers and technology institutions to have a better view of what to use in their projects, reducing spending on choice time. tool, database choice, decrease of reworks and delays.